O “DNApraQ?” como espaço de aprendizado mútuo: relato de experiência pessoal em divulgação científica - Massone, Luís Mário Nicoletti (Universidade Federal de São Carlos, 2025)
Personal experience is one of the most enriching forms of learning, allowing the interaction with different contexts and people. This work explores my experience as a member of the science communication group “DNA pra Q?”, an initiative created at the Federal University of São Carlos, Araras campus. The report details the activities carried out by the group, such as the production of educational content for social media, the organization of in-person events, and the conduction of practical workshops, highlighting the impact of these actions in combating scientific misinformation, especially in a scenario marked by the times during and post-COVID-19 pandemic. Based on these experiences, I describe the knowledge acquired both academically and personally. My participation in the project provided the development of essential skills such as leadership, communication, and teamwork, as well as broadening my understanding of the role of science in society. Direct contact with a heterogeneous group and with the public reinforced the importance of empathy and mutual learning in this process, especially in the context of teacher education. Furthermore, it highlights how initiatives similar to “DNA pra Q?” promote a more open dialogue between science and society since, through active engagement with different audiences, these actions help to demystify incorrect concepts, combat scientific misinformation, and strengthen critical thinking. It is concluded that projects of this nature not only assist in training future educators but also represent an opportunity to establish transformative connections for a more accessible and collaborative science.
“DNAforwhat?” as a space for mutual learning: a personal experience report in scientific dissemination
Keywords: Desinformação científica; Divulgação científica; Relato de experiência; Scientific misinformation; Scientific dissemination; Science; CIENCIAS BIOLOGICAS::GENETICA